Longitudinal assessment of maternal-fetal Doppler parameters and maternal plasma level of matrix metalloproteinases 2 and 9 - Jorge Neto, Salim Demétrio; Machado, Jackeline Souza Rangel; Araujo Júnior, Edward; Palei, Ana Carolina Taveiros; Amaral, Lorena Machado; Tanus-Santos, José Eduardo; Marcolin, Alessandra Cristina; Duarte, Geraldo; Sandrim, Valéria Cristina [UNESP]; Cavalli, Ricardo Carvalho (My University, 2016)
Objective: To assess the behavior as well as the comparison between maternal circulating level of biochemical markers (matrix metalloproteinases - MMP-9 and MMP-2) and maternal-fetal Doppler parameters in all three trimesters of pregnancy. Methods: We performed a prospective longitudinal study with 33 healthy pregnant women in three periods of pregnancy: A1 (12w0–14w6d), A2 (22w0d–24w6d) and A3 (34w0d and 36w6d). The following maternal Doppler parameters were assessed: mean pulsatility index (PI) uterine artery, resistance index (RI) umbilical artery and RI middle cerebral artery. The maternal plasma concentrations of MMP-2 and MMP-9 were determined by enzyme immunoassay (ELISA). To compare two (A2 and A3) and three assessments (A1, A2 and A3), we used the paired Student t test and linear regression, respectively. To compare the biomechanical markers and maternal-fetal Doppler parameter, we used the Spearman correlation coefficient (ρ). Results: We observed a significant decrease of PI uterine artery Doppler over the three trimesters of pregnancy (p < 0.01) and RI umbilical artery Doppler overt second to three trimester of pregnancy (p < 0.05). We did not observe significant difference in the maternal plasma level of MMP-2 and MMP-9 between the three trimesters. We did not also observe significant correlation between biochemical markers and maternal-fetal Doppler parameters. Conclusion: Maternal circulating level of MMPs did not modify throughout pregnancy and it did not show correlation with maternal-fetal Doppler parameters.
Keywords: Biochemical markers; Doppler; matrix metalloproteinases; pregnancy